Recent Advances in the Research and Development of Marine Antimicrobial Peptides - El-Gamal, Mohammed I.; Abdel-Maksoud, Mohammed S.; Oh, Chang-Hyun (BENTHAM SCIENCE PUBL LTD, 2013)
Antimicrobial peptides are a group of natural or semi-synthetic molecules possessing antimicrobial activities against bacteria, fungi, viruses, parasites, etc. They are considered as promising candidates for treatment of microbial infections and suppression of microbial resistance. The increasing emergence of bacterial resistance has required development of new efficient antibiotics that can be added to the antibacterial armamentarium. The marine world provides a rich source of antimicrobial peptides. That world has not been highly explored yet, and much more effort is required in order to discover new efficient antimicrobial peptides. In the present article, we have reviewed the recent progress in the field of marine antimicrobial peptides from 2009 until the mid of 2012.
Keywords: FUNCTIONAL-CHARACTERIZATION; ANTIBACTERIAL; EPINECIDIN-1; DEPSIPEPTIDE; MECHANISM; INFECTION; PISCIDIN; PROTEIN